SHORT syndrome in an 11-year-old boy – case report - Badeński, Andrzej; Stojewska, Małgorzata; Ziora, Katarzyna; Badeńska, Marta; Bjanid, Omar; Sobczyńska-Tomaszewska, Agnieszka; Wolnowska, Monika; Szczepańska, Maria (Pediatria Polska - Polish Journal of Paediatrics, 2019)
SHORT syndrome is a rare inherited autosomal-dominant disease. It has been clinically defined by its acronym: short stature, hyperextensibility of joints or hernia or both, ocular depression, Rieger abnormality, and teething delay. The prevalence of SHORT syndrome in the general population is still unknown. In this manuscript, we would like to present an 11-year-old boy with SHORT syndrome. He presented hypostature (121.3 cm) and low body weight (19.6 kg) in clinical examination. Furthermore, shortening of the forearm bones, incomplete teeth, and dysmorphia of the face (triangular-shaped face, prominent forehead, eye depression, narrow nose, slightly bent downwards, corners of the mouth directed downwards) were noticed. Molecular analysis of selected regions of the phosphatidylinositol 3 kinase-PIK3R1 gene showed the mutation Arg649Trp (R649W) in one allele of the PIK3R1 gene (in a heterozygous system). The authors believe that this case report will draw attention to detecting the clinical features of SHORT syndrome, which allows for adequate diagnosis and treatment.